Ambrogio Leone's De Nola, Venice 1514 : humanism and antiquarian culture in Renaissance southern Italy - De Divitiis, Bianca; Lenzo, Fulvio; Miletti, Lorenzo (Brill's studies in intellectual history, 2018)
"This volume offers the first multidisciplinary study of the De Nola (Venice 1514), a hitherto underestimated Latin work written by the Nolan humanist and physician Ambrogio Leone. Furnished by four pioneering engravings made with the help of the Venetian artist Girolamo Mocetto, the De Nola is an impressively rich and multifaceted text, which contains an antiquarian (and celebrative) study of the city of Nola, in the Kingdom of Naples. By describing antiquities, inscriptions, buildings, but also social and religious aspects, the De Nola offers a precious insight of a southern Italy centre in the Renaissance, and constitutes a refined example of 16th century antiquarianism. The work is analysed through an interdisciplinary approach, encompassing art and architecture history, antiquarianism, literature, social history, and anthropology"--